A CFD analysis to investigate thermal losses in a panel composed of several CPC concentrators. (March 2018) - Francesconi, Marco; Antonelli, Marco
Highlights: Experimentally validated CFD approach. The efficiency of a whole panel composed by several CPCs was evaluated. Several flow patterns and the respective thermal losses were discussed. The thermal efficiency was influenced by the number of CPCs and their arrangement. A double glass coverage was considered to reduce thermal losses. The double glass was useful for low incoming radiation intensities. The use of a suitable gap of truncated CPCs improved the global efficiency of the whole panel. The panel containing several CPCs is a key factor in the design of a solar field. Abstract: The work presented in this paper deals with the numerical analysis of the heat transfer in a panel containing several compound parabolic collectors (CPCs). The methodology was based on a CFD approach previously validated in a paper available in literature. The aim of the research was the evaluation of the thermal heat losses in the panel considering different arrangement of the CPCs. In particular, the position of each CPC influences the value of the thermal efficiency, because of the values of the different thermal resistance between the absorber and the external environment. Moreover, as second step, the presence of an external glass was simulated. The results highlighted a reduction of five percentage points of the thermal efficiency; the reason was due to the reduction of the optical efficiency that was stronger than the minimization of thermal losses. However, it was also found that the presence of an external glass may be useful at low incoming radiation. In the end, the use of truncated collectors was investigated to highlight the variation of performances of the whole panel. The main effect of the truncation was the variation of the shape of pathlines of the filling fluid, that was noticeable for the highest value of the simulated gap; in particular, the panel efficiency increased of two percentage points. The results of this work suggest that a suitable configuration of the panel might be considered in the design of the solar field, to increase the efficiency of the system.